K-feldspar megacryst accumulations formed by mechanical instabilities in magma chamber margins, Asha pluton, NW Argentina. (July 2018) - Rocher, Sebastián; Alasino, Pablo H.; Grande, Marcos Macchioli; Larrovere, Mariano A.; Paterson, Scott R.
Abstract: The Asha pluton, the oldest unit of the San Blas intrusive complex (Early Carboniferous), exhibits impressive examples of magmatic structures formed by accumulation of K-feldspar megacrysts, enclaves, and schlieren. Almost all recognized structures are meter-scale, vertically elongate bodies of variable shapes defined as fingers, trails, drips, and blobs. They preferentially developed near the external margin of the Asha pluton and generally are superimposed by chamber-wide magmatic fabrics. They mostly have circular or sub-circular transverse sections with an internal fabric defined by margin-parallel, inward-dipping concentric foliation and steeply plunging lineation at upper parts and flat foliation at lower parts. The concentration of megacrysts usually grades from upper sections, where they appear in a proportion similar to the host granite, to highly packed accumulations of K-feldspar along with grouped flattened enclaves at lower ends. These features suggest an origin by downward localized multiphase magmatic flow, narrowing and 'log jamming', and gravitational sinking of grouped crystals and enclaves, with compaction and filter pressing as main mechanisms of melt removal. Crystal size distribution analysis supports field observations arguing for a mechanical origin of accumulations. The magmatic structures of the Asha pluton represent mechanical instabilities generated by thermal and compositional convection, probably owing to cooling and crystallization near the pluton margins during early stages of construction of the intrusive complex. Graphical abstract: Image 1 Highlights: K-feldspar megacryst accumulations of the Asha pluton are described in detailed outcrop maps. The accumulations are a result of deformation by downward multiphase magmatic flow due mechanical instabilities. Flow narrowing and 'log jamming' produce compaction and filter pressing, which are the main mechanisms of accumulation. The instabilities are promoted by thermal and compositional effects of cooling and crystallization near pluton margins.